Central retinal artery occlusion following severe blow-out fracture in young adult - Noriko Himori (Dove Medical Press, 2009)
Noriko Himori, Hiroshi Kunikata, Takaaki Otomo, Nobuo Fuse, Kohji NishidaDepartment of Ophthalmology and Visual Science, Tohoku University Graduate School of Medicine, Sendai, JapanAbstract: A 20-year-old woman was involved in a traffic accident while riding a motorcycle. The vision in her right eye was severely reduced. At the first examination, the eyelids of her right eye were severely swollen, and the eye could barely be seen. The fundus was not visible. She had no light perception in her vision. Computed tomography revealed a severe blow-out fracture in her right eye. Surgery was immediately performed to correct the fracture and the eye globe was replaced in the orbit. On the fourth postoperative day, the right fundus was visible and a cherry-red spot and milky-white edema were seen. Fluorescein angiography showed an arterial filling defect. Four months later, her visual acuity was light perception. Our case shows that a central retinal artery occlusion can be a complication of a blow-out fracture of the lower orbital wall and can lead to severe visual loss even with early surgical repair.Keywords: central retinal artery occlusion, blow out fracture, trauma, young adult